Follow up valuation and further actions for additional wall works of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding follow up valuation and further actions for additional wall works of BRAC University new campus project.